2020
DOI: 10.1039/d0fo00188k
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of insectAlphitobius diaperinustowards the development of bioactive peptide hydrolysates

Abstract: Edible insects are a promising protein source for the future generation, due to their nutritional composition, sustainability and low environmental impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 54 publications
0
42
1
Order By: Relevance
“…The combination of Flavourzyme TM 500L and Alcalase TM 2.4L (run 4) resulted in an increase of 62% in ABTS radical scavenging activity of the protein hydrolysates compared to the control sample. The antioxidant activity values were higher than those obtained for lesser mealworm ( Alphitobius diaperinus) hydrolyzed with Alcalase 2.5L (E:S ratio of 1.5% for 4 hr) and Corolase PP (E:S ratio of 3% for 6 hr), in which both hydrolysates presented ABTS radical scavenging activities of approximately 95 µmol TEq g −1 (Sousa, Borges, & Pintado, 2020).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The combination of Flavourzyme TM 500L and Alcalase TM 2.4L (run 4) resulted in an increase of 62% in ABTS radical scavenging activity of the protein hydrolysates compared to the control sample. The antioxidant activity values were higher than those obtained for lesser mealworm ( Alphitobius diaperinus) hydrolyzed with Alcalase 2.5L (E:S ratio of 1.5% for 4 hr) and Corolase PP (E:S ratio of 3% for 6 hr), in which both hydrolysates presented ABTS radical scavenging activities of approximately 95 µmol TEq g −1 (Sousa, Borges, & Pintado, 2020).…”
Section: Resultsmentioning
confidence: 77%
“…According to Sousa et al. (2020), the antioxidant properties of peptides are associated with their amino acid composition. Hydrophobic amino acids, such as alanine, valine, isoleucine, leucine, proline, and methionine, have electrons that can be donated to eliminate free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatic hydrolysis was realized using alcalase enzyme according to Sousa et al [35] with modifications. The enzyme/substrate (E:S) ratio was fixed at 1:10 (w/w) and the reaction was done under agitation 100 rpm at 55 • C, pH 8.0, for 180 min.…”
Section: Enzymatic Hydrolysis and Combined Treatmentsmentioning
confidence: 99%
“…Investigations on techno-functional properties including solubility, water- and oil-binding capacity, foaming capacity, surface hydrophobicity, gelling properties, coagulation properties, and the emulsifying ability of various insect powders, and their protein extracts have already shown promising outcomes [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In addition, enzymatic hydrolysis of the protein extracts could efficiently enhance their functionalities and obtain bioactive peptides with antioxidative, antihypertensive, antidiabetic, and antimicrobial properties [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Regarding studies in emulsions stabilized with insect proteins, Wang et al [ 43 ] reported a superior performance of black soldier fly ( Hermetia illucens ) protein concentrate on emulsifying a high fraction (40 wt%) of lemon oil compared to whey protein isolate (WPI), and Gould and Wolf [ 44 ] found that sunflower oil emulsions stabilized with mealworm protein displayed smaller droplet size and a lower protein concentration was required compared to WPI; in addition, the produced emulsion also showed great stability under wide environmental stresses (temperature at −20 °C and 60–90 °C, pH 3–8 and ionic strength 80–330 mM).…”
Section: Introductionmentioning
confidence: 99%